2010
DOI: 10.1590/s1678-77572010000600013
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical expression of vascular endothelial growth factor and matrix metalloproteinase-9 in radicular and residual radicular cysts

Abstract: ObjectiveThis study assessed and compared the immunoexpression of vascular endothelial growth factor (VEGF) and matrix metalloproteinase-9 (MMP-9) in radicular cysts (RCs) and residual radicular cysts (RRCs), relating them to the angiogenic index and the intensity of the inflammatory infiltrate. Material and MethodsTwenty RCs and 10 RRCs were evaluated by immunohistochemistry using anti-VEGF and anti-MMP-9 antibodies. The angiogenic index was determined by microvessel count (MVC) using anti-von Willebrand fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
17
0
1
Order By: Relevance
“…An increase in inflammatory cells can result in propagation of cytokines and chemokines, some of which are angiogenic (22). Microvessel count and MVD and have been found to be higher in cysts with more accentuated inflammation (20,23). Moreover, angiogenesis itself can upregulate inflammation through fascilitating and increasing transportation of inflammatory cells, providing oxygen and nutrients to the site harboring inflammation and finally increased secretion of inflammation attracting factors due to the existence of a higher number of endothelial cells in the region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in inflammatory cells can result in propagation of cytokines and chemokines, some of which are angiogenic (22). Microvessel count and MVD and have been found to be higher in cysts with more accentuated inflammation (20,23). Moreover, angiogenesis itself can upregulate inflammation through fascilitating and increasing transportation of inflammatory cells, providing oxygen and nutrients to the site harboring inflammation and finally increased secretion of inflammation attracting factors due to the existence of a higher number of endothelial cells in the region.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore maybe the extremely high number of inflammatory cells in radicular cysts contributed to the significant difference found in the MVD score between the KCOTs and RCs evaluated in the current investigation. In RCs, there is a continuous secretion of bacterial toxins from the infected root canal which leads to a constant migration of inflammatory cells to the region (23,24). This is in contrast to the one-time entrance of inflammation to the fibrous wall of KCOTs following a single exposure through the cortical bone (3,4).…”
Section: Discussionmentioning
confidence: 99%
“…29 VEGF was studied in radicular and residual cysts by Ruitz et al, and its expression in epithelial lining of cysts might be important for the enlargement of these lesions and VEGF might play important roles in the angiogenesis in residual cysts and radicular cysts. 30 Mitrou et al studied VEGF in odontogenic cysts, which was expressed in the epithelium of odontogenic keratocysts, dentigerous cysts, and radicular cysts in varying intensity, and concluded that VEGF expression by the odontogenic epithelium is not induced solely by inflammation. 31 Leonardi et al studied detection of VEGF/VPF in periapical lesions, using anti-VEGF antibody and observed that, in periapical granulomas without epithelium, almost all of the inflammatory cells were immunoreactive to anti-VEGF/VPF antibody.…”
Section: Expression Of Vegf In Odontogenic Cysts and Tumorsmentioning
confidence: 99%
“…Collectively they are capable of degrading all kinds of extracellular matrix proteins. Also, they play an important role in tissue remodeling associated with various physiological and pathological processes such as morphogenesis, angiogenesis, tissue repair, cirrhosis, arthritis and metastasis (8,9). Normal human osteoblasts express MMP-2 and in vitro, they secrete abundant MMP-2.…”
Section: Fluoride Modulates Preosteoblasts Viability Andmentioning
confidence: 99%